Resisting excessive anxiety and worry by a tenth century Islamic philosopher - Moris, Megawati (2021)
Resisting Excessive Anxiety and Worry These two dispositions are affections of the reason. They can be present in excess or lack. Excessive activity of the rational soul: Give the body repose from them Preoccupy it in as much diversion, amusement and pleasure as it requires to keep it fit and maintain it in good health. Otherwise the body will weaken, become wasted and then collapse; this will prevent us from reaching our goal. This diversion and pleasure are not for their own sake but to strengthen us to reach our purpose as quickly as possible. People vary in the amount of anxiety and worry they can bear. The power of endurance needs to be monitored and increased as much as possible through habit. Example: The man who wanted to study philosophy and rival the great philosophers e.g. Socrates, Plato etc Result of long hours of thinking: less intake of food, insomnia, wasting away, victim of delusion and depression. But far from reaching his goal. Similarly for the person who has shortcomings. Conclusion: It is incumbent on us to be moderate in our anxieties and worries if we want to reach our goals.